"Those on the Right Take Chloroquine": The Illiberal Instrumentalisation of Scientific Debates during the COVID-19 Pandemic in Brasil. Issue 2 (3rd April 2021) - Oliveira, Thaiane; Evangelista, Simone; Alves, Marcelo; Quinan, Rodrigo
Abstract : Since the beginning of the COVID-19 pandemic, the Brasilian government has undergone a significant political dispute over the use of hydroxychloroquine as a measure to confront the disease and contested scientific and healthcare organisations findings related to the drug's effectiveness. In this article, we seek to understand the manner in which an illiberal populist government and the supporters thereof refer to scientific discourse during the pandemic, with a focus on the debates on Brasilian far-right networks on Twitter. Using a mixed methodology with statistical methods, social media analysis, natural language processing and qualitative content analysis, this study seeks to investigate which sources and stakeholders were referenced and the narratives that structured the arguments of far-right supporters who defended the use of hydroxychloroquine. The results highlight the use of sources that are ideologically aligned to the right and a reconfiguration of scientific authority that was supported by illiberal values. Among the main discourses, we observed an epistemic challenge with a partisan bias, which led to the scientific authority legitimising some arguments and discrediting others. We also identified the spread of conspiracy theories that reflected the epistemic challenge, in addition to conservative, revivalist and individualistic postures.